HPV Vaccination in Correctional Care: Knowledge, Attitudes, and Barriers Among Incarcerated Women. (July 2019) - Moore, Alia; Cox-Martin, Matthew; Dempsey, Amanda F.; Berenbaum Szanton, Katie; Binswanger, Ingrid A.
Incarcerated women are at increased risk of developing cervical cancer and have high rates of human papillomavirus (HPV) infection, an important cause of cervical cancer. However, many correctional facilities do not offer HPV vaccination to female inmates. This pilot survey study, conducted with incarcerated women aged 18 to 26 at a facility that does not offer the vaccine, assessed attitudes and knowledge about HPV and the HPV vaccine, acceptability of and barriers to in-prison HPV vaccination, and self-reported HPV vaccination rates. Most participants reported that they had not received the HPV vaccine but had positive attitudes toward it and would be willing to get it in prison. Correctional facilities should consider offering this preventive service to this vulnerable population.